Late-Stage C–H Deuteration of Organic Compounds via Ligand-Enabled Palladium-Catalyzed Hydrogen Isotope Exchange - Dey, Jyotirmoy; van Gemmeren, Manuel (Synlett, 2024)
Over the past years our lab has established a research program towards the late-stage introduction of deuterium into organic molecules using Pd-catalyzed reversible C–H activation as a means to affect hydrogen isotope exchange. Through catalyst design, including the introduction of novel ligand scaffolds, as well as the use of strategically chosen optimization and screening approaches, e.g., exploiting microscopic reversibility by first optimizing de-deuteration processes or using a multi-substrate screening approach, our studies have resulted in a number of synthetically useful labelling protocols and are described herein from a personal perspective.1 Introduction2 β-C(sp3)–H Deuteration of Free Carboxylic Acids3 Nondirected C–H Deuteration of Arenes4 Nondirected C–H Deuteration of Heteroarenes5 Conclusion
Keywords: deuteration; hydrogen isotope exchange (HIE); catalysis; ligand design; labelling